Cloning of 1– fructan: fructan fructosyltransferase gene and expression of recombinant 1– fructan: fructan fructosyltransferase in yeast - Ngampanya, Budsaraporn; Boonchoo, Kriengsak (Asia-Pacific Journal of Science and Technology, 2016)
Fructosyltransferases (FTases) were important enzymes for fructo-oligosaccharides (FOS) synthesis. Recently, FOS was considered as a potential prebiotic in food industry. In particularly, FOS with short chains was used as a new alternative sweetener. The production of recombinant 1- fructan: fructan fructosyltransferase (1- FFT) in yeast system was conducted in this research. The 1- fructan: fructan fructosyltransferase gene (1- fft) cloned from 105 days old tuber of Kaentawan (Helianthus tuberosus L.) was sub cloned to expression vector, pPICZαB by adding PstI and SacII sites. The cloned gene was successfully transformed to yeast Pichia pastoris X-33 by lithium chloride transformation method. The yeast transformant; P. pastoris X- 33 PF1 showed the ability to produce recombinant 1- FFT. The enzyme activity at 3.57 and 3.33 unit/L was determined in cell and culture medium, respectively. It was also found that FOS was synthesized when recombinant 1- FFT was incubated with 1- kestose and synthesized FOS as substrates. The synthesis of FOS was not detected when sucrose was used as substrate of recombinant 1- FFT.